Influence of magnetic field exposure and clay mineral addition on the fractionation of Greek yogurt whey components - Kyle, Clinton (Kansas State University, 2015)
Greek yogurt is one of the largest-growing sectors in the dairy industry accounting for over 25% of yogurt sales in the United States. Greek yogurt is produced by removing a portion of water and water soluble components from yogurt. Consequently, a large quantity of Greek yogurt whey (GYW) is being produced as a co-product. GYW is compositionally different from cheese whey, and thus poses economic and environmental challenges to the dairy industry. The objective of the present study was to evaluate two physical treatments as alternative methods for separating valuable GYW components: magnetic fluid treatment (MFT) and the addition of sepiolite, a clay mineral. A MFT chamber was designed using four pairs of neodymium magnets arranged to produce a magnetic field strength of 0.6 Tesla. Three batches of GYW each from two manufacturers were procured. A 2×3 factorial design was used with MFT or without MFT and the addition of zero, two, or four grams of sepiolite per 100g of GYW. The pH of GYW was adjusted to 7.2 using 5N NaOH solution, and the GYW was pumped at a rate of 7.5 L/min through the MFT system with or without MFT chamber attached. The sample was split into three sub-samples, heated to 80°C, and sepiolite was added as per the experimental design. The samples were centrifuged at 1,000g for five minutes. The top aqueous layer was separated and analyzed for total solids, ash, lactose, protein, calcium, phosphates, and sodium content along with color. MFT did not influence the analyzed whey components (P > 0.05) except for lactose. However, addition of sepiolite influenced protein content and a* and b* color values for the top aqueous layers (P < 0.05). Both levels of sepiolite addition resulted in about a 50% decrease in protein compared to original GYW. Adding two grams of Sepiolite per 100g of GYW from manufacturer 1 resulted in b* decreasing from 25.99 to 8.16 compared to treated GYW with no sepiolite. Sepiolite was found to have possible applications in the removal of proteins and color pigments in GYW.
Keywords: Greek yogurt whey; Sepiolite; Magnetic fluid treatment; Clay; Magnet; Whey; Food Science (0359)